National Survey of Jails: Jurisdiction-Level and Jail-Level Data, 1986 ([Verlag nicht ermittelbar], 1988)
This data collection provides annual data on jail populations across the nation and examines the "spillover" effect on local jails resulting from the dramatic growth in federal and state prison populations. These data permit an assessment of the demands placed on correctional resources. Information is available on the number of inmates by sex, race, adult or juvenile status, reason being held, and cause of death.